Producing Trust Among Illicit Actors: A Techno-Social Approach to an Online Illicit Market. (September 2020) - Bancroft, Angus; Squirrell, Tim; Zaunseder, Andreas; Rafanell, Irene
Illicit market exchanges in cybercriminal markets are plagued by problems of verifiability and enforceability: trust is one way to ensure reliable exchange. It is fragile and hard to establish. One way to do that is to use the administrative structure of the digital market to control transactions. This is common among a specific type of market – darknet cryptomarkets. These are sites for the sale of illicit goods and services, hosted anonymously using the Tor darknet. However, reliance by users on the technology and the market administrators exposes users to excessive risk. We examine a case of a market that rejects several key technological features now common in cryptomarkets but that is nonetheless reliable and robust. We apply a techno-social approach that looks at the way participants use and combine technologies with trust relationships. The study was designed to capture the interactional context of the illicit market. We aimed to examine both person-to-person interaction and the technical infrastructure the market relied on. We find that the social space of the market maintains itself through a shared common security orientation, community participation in key decisions about products sold, performing trust signalling, and relying on lateral trust between members. There are implications for how resilience in cryptomarkets is understood.